Post-traumatic stress disorder, depression, anxiety, and their predictors among internally displaced persons in a conflict-affected area of Metekel Zone, Northwest Ethiopia: structural equation modeling - Bekeko, Solomon Debela; Mekonnen, Fantahun Ayenew; Teklu, Rediet Eristu (Frontiers in Psychiatry, 2025)
IntroductionInternally displaced persons (IDPs) are people forced to leave their homes due to natural or man-made disasters. Mental health illnesses were linked to conflict and displacement. Post-traumatic stress disorder, depression, and anxiety have the highest rates. However, there are few studies on mental health among internally displaced persons in conflict-affected areas in Ethiopia. To fill this information and methodological gap, structural equation modeling was used to investigate the direct and indirect effects of factors.ObjectiveThe study aimed to assess the magnitude and determinants of post-traumatic stress disorder, depression, and anxiety among internally displaced persons in the conflict area of Metekel Zone, Northwest Ethiopia, 2023.MethodA community-based cross-sectional study was conducted among 1,042 participants selected by systematic sampling. Data were collected using face-to-face interviews, and structural equation modeling was used to assess the interrelationship among the variables.ResultThe magnitude of anxiety, post-traumatic stress disorder, and depression was 74.56%, 76.9%, and 79.53%, respectively. Being female, death of a loved one displaced two times, and social support were factors that affected anxiety. The significant factors for post-traumatic stress disorder were being female, death of a loved one, social support, and anxiety. In addition to the significant independent variables, the factors anxiety and post-traumatic stress disorder had an impact on depression.ConclusionThe magnitude of anxiety, post-traumatic stress disorder, and depression was found to be high. Older-aged IDPs, female IDPs, and those who were not supported by friends or the government were found to be most at risk. Emphasis is needed on the promotion of mental health practices for internally displaced persons due to a conflict, especially for IDPs with poor social support and who have a history of death of loved ones.